Development of A Mobile-Based Screening and Educational Application For Adolescent Depression Prevention: A Mixed Methods Approach - Afifatul Mukaromah; Rizki Fitryasari P. K; Kristiawati Kristiawati (Jurnal Ners, 2026)
Adolescence is a developmental period characterized by biological, cognitive, and psychosocial changes that increase vulnerability to depression. Early identification of adolescent depression is challenging due to overlapping symptoms with normal emotional changes, while digital technology provides accessible approaches for depression prevention. This study aimed to develop a depression screening and educational application to prevent depression among adolescents. Methods this study employed an exploratory sequential mixed methods design consisting of three stages: qualitative exploration, mobile application development, and quantitative evaluation. Qualitative data were collected through focus group discussions, while the quantitative phase involved expert feasibility assessment and usability testing using the System Usability Scale (SUS). Results the findings from phase 1 identified four themes of adolescent depressive symptoms: cognitive, affective, behavioral, and motivational, which were used to develop the screening content. Educational needs related to adolescent depression were classified into informational, motivational, and behavioral aspects, forming the educational content. Phase 2 resulted in the development of an android based application integrating depression screening and preventive education. In phase 3, expert assessment indicated that the application prototype content and features were feasible for use, and usability testing among 10 adolescents demonstrated good usability based on SUS evaluation.  Conclusion therefore, the application has the potential to be a user-friendly digital platform for adolescent depression prevention. However, further studies are needed to evaluate its effectiveness in preventing adolescent depression.